The wilds - Pearse, Sarah (Elin Warner, 2024)
"Detective Elin Warner unravels the mystery behind the disappearance of a young woman in a propulsive new thriller from the New York Times bestselling author of The Sanatorium. Since the dark events that scarred her childhood, Kier Templer escaped her hometown to live life on the road. She and her twin have never lost contact until, on a trip to a Portuguese national park, Kier vanishes without a trace. Detective Elin Warner arrives in the same park ready to immerse herself in its vast wilderness--only to hear about Kier's disappearance, and discover a disturbing map she left behind. The few strangers at an isolated campsite close ranks against Elin's questions, and the park's wild beauty starts to turn sinister. Elin must untangle the clues to find out what really happened to Kier. But when you follow a trail, you have to be careful to watch your back... Sarah Pearse brilliantly introduced readers to Elin Warner in The Sanatorium, with her exploits continuing in The Retreat; here, the series concludes with The Wilds, where the unanswered questions plaguing Elin are finally resolved"--